The Effectiveness of the Fading Method and the Use of Color in Improving Reading Ability: Efektifitas Metode Fading dan Penggunaan Warna dalam Meningkatkan Kemampuan Membaca - Nor Fatmah; Noor Alkaff; Ainun Alkaff (Sangkalemo : The Elementary School Teacher Education Journal, 2022)
Reading skills are one of the skills that have an important role in human life. Reading is a mental process where there is process of translating visual codes into meaningful spoken language. The purpose of the reading process is to receive or understand the message contained in the text or writing. In this case, some students have difficulty in reading, which causes the demands for learning to be unfulfilled. This is due to the lack of stimulus provided during the learning process so that there is a decrease in students' reading ability, then the fading method and the use of color become interventions in improving the ability and fluency of reading in elementary students. The method used is a single subject, to see the effectiveness of a behavior modification approach with the fading method and the use of color to improve reading skills. In exploring the data, interviews, observation, and psychological tests in the form of the WISC IQ test were used, and informal reading tests were used. The results of the intervention showed that there was an increase in students' reading fluency by using the fading method and the use of color.